2016
DOI: 10.1039/c5nr07695a
|View full text |Cite
|
Sign up to set email alerts
|

Novel mesoporous P-doped graphitic carbon nitride nanosheets coupled with ZnIn2S4nanosheets as efficient visible light driven heterostructures with remarkably enhanced photo-reduction activity

Abstract: In this report, we rationally designed and fabricated P-C3N4/ZnIn2S4 nanocomposites by in situ immobilizing ZnIn2S4 nanosheets onto the surface of mesoporous P-doped graphite carbon nitrogen (P-C3N4) nanosheets in a mixed solvothermal environment; their application to the photoreduction of 4-nitroaniline was used to estimate the photocatalytic performance. Different to the template route, here the mesoporous P-C3N4 nanosheets were prepared with a template-free strategy. The as-fabricated P-C3N4/ZnIn2S4 nanocom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(90 citation statements)
references
References 44 publications
4
86
0
Order By: Relevance
“…(3.2*10 −1  A/m −2 )43, Wei et al . (2.4*10 −5  A/m −2 )44 and Gui et al . (1.75*10 −1  A/m −2 ), our sample possesses a highest photocurrent of (7.04*10 −1  A/m −2 ), indicating the higher separation efficiency of electron-hole pairs.…”
Section: Resultsmentioning
confidence: 84%
“…(3.2*10 −1  A/m −2 )43, Wei et al . (2.4*10 −5  A/m −2 )44 and Gui et al . (1.75*10 −1  A/m −2 ), our sample possesses a highest photocurrent of (7.04*10 −1  A/m −2 ), indicating the higher separation efficiency of electron-hole pairs.…”
Section: Resultsmentioning
confidence: 84%
“…As shown in Figure 1, conventional gC 3 N 4 based type II heterojunction system is effective for separating photogenerated electron-hole pairs due to the staggered band structures of the component semi conductors. Various metal oxides (TiO 2 , [83][84][85][86][87][88] ZnO, [89] WO 3 , [90][91][92] CeO 2 , [93][94][95] In 2 O 3 , [96][97][98] MoO 3 , [99] SnO 2 , [100][101][102][103][104] Fe 2 O 3 , [105,106] V 2 O 5 ), [107,108] metal sulfides (CdS, [109][110][111][112][113][114] ZnS, [115][116][117] MoS 2 , [118] Zn 1−x Cd x S, [119] ZnIn 2 S 4 ), [120][121][122] halides (BiOI, [123] BiOCl, [124,125] BiOBr, [126] AgI, [127][128]…”
Section: G-c 3 N 4 -Based Conventional Type II Heterojunction Systemsmentioning
confidence: 99%
“…BiOI with a narrow band gap (1.94 eV) shows good photoresponse under visible light. Figure 5a shows the schematic diagram for the facile and largescale preparation of the gC 3 TiO 2 /g-C 3 N 4 Photocatalytic hydrogen generation Two times higher than g-C 3 N 4 [85] TiO 2 /g-C 3 N 4 Photodegradation of MB and reduction of Cr(VI) ions / [83] ZnO/g-C 3 N 4 Photodegradation of MO and p-nitrophenol Three times higher than g-C 3 N 4 (MO), six times higher than g-C 3 N 4 (p-nitrophenol) [89] ZnO/g-C 3 N 4 Photocatalytic degradation of rhodamine B (RhB) / [154] WO 3 /g-C 3 N 4 Photodegradation of MB 4.2 times and 2.9 times higher than that of the pure WO 3 and pure g-C 3 N 4 [90] WO 3 /g-C 3 N 4 Photodegradation of acetaldehyde (CH 3 CHO) / [91] WO 3−x /g-C 3 N 4 Photocatalytic degradation of MO Three times higher than g-C 3 N 4 [155] CeO 2 /g-C 3 N 4 Photocatalytic degradation of phenol and NO removal 17.3 times higher than g-C 3 N 4 , 68.5 times higher than CeO 2 (phenol) [95] N-doped CeO x /g-C 3 N 4 Photocatalytic hydrogen generation 2.2 times higher than g-C 3 N 4 [156] In ZnS/g-C 3 N 4 Photocatalytic degradation of RhB 37.8 and 2.8 times higher than that of the pure ZnS and g-C 3 N 4 [116] CdS/g-C 3 N 4 Photocatalytic degradation of MB Three times higher than g-C 3 N 4 [110] MoS 2 /g-C 3 N 4 Photocatalytic hydrogen generation / [118] MoS 2 /g-C 3 N 4 Photocatalytic degradation of RhB 4.2 times higher than g-C 3 N 4 [152] MoS 2 /g-C 3 N 4 Photocatalytic degradation of MO / [159] ZnIn 2 S 4 /P-doped g-C 3 N 4 Photoredox of 4-nitroaniline / [122] Zn 0.8 Cd 0.2 S/P-doped g-C 3 N 4 Photocatalytic degradation of MB / [160] Ag 3 VO 4 /g-C 3 N 4 Photocatalytic degradation of RhB 5.8 times higher than g-C 3 N 4 [161] Ag 3 PO 4 /g-C 3 N 4 Photocatalytic degradation of MO Four times higher than Ag 3 PO 4 [162] Ag 3 PO 4 /g-C 3 N 4 Photocatalytic degradation of MO Five times higher than g-C 3 N 4 , 3.5 times higher than Ag 3 PO 4 [163] BiVO 4 /S-doped g-C 3 N 4 Photocatalytic oxygen generation >2 times higher than g-C 3 N 4 [164] BiVO 4 /g-C 3 N 4 Photocatalytic degradation of MB 4.5 and 6.9 times higher than that of the pure BiVO 4 and g-C 3 N 4 [165] BiPO 4 /g-C 3 N 4 Photocatalytic degradation of MB / [138] Bi 2 WO 6 /g-C 3 N 4 Photocatalytic degradation of RhB Five and 9 times higher than that of the pure...…”
Section: G-c 3 N 4 -Based Conventional Type II Heterojunction Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…This TiO 2 /g-C 3 N 4 /FeP configurations ignificantly improves charges eparation and transfer capability.A saresult, our nonnoble-metal photoelectrochemical system yields outstanding visiblel ight (> 420 nm) photocurrent:a pproximately 0.3 mA cm À2 at 1.23 Va nd 1.1 mA cm À2 at 2.0 Vv ersus RHE, which is the highest for ag -C 3 N 4 -based photoanode. [26][27][28][29][30] The authors attribute such observed advantages mainlyt ot he efficient usage of visible light as ar esult of the modified band structure. B, O, and P) [13,[16][17][18][19][20][21][22] doping has been explored, leadingt oa ttractive progress.…”
Section: Introductionmentioning
confidence: 99%